2020
DOI: 10.1111/jpi.12684
|View full text |Cite
|
Sign up to set email alerts
|

A PERIOD3 variable number tandem repeat polymorphism modulates melatonin treatment response in delayed sleep‐wake phase disorder

Abstract: We examined whether a polymorphism of the PERIOD3 gene (PER3; rs57875989) modulated the sleep-promoting effects of melatonin in Delayed Sleep-Wake Phase Disorder (DSWPD). One hundred and four individuals (53 males; 29.4 ±10.0 years) with DSWPD and a delayed dim light melatonin onset (DLMO) collected buccal swabs for genotyping (PER3 4/4 n = 43; PER3 5 allele [heterozygous and homozygous] n = 60). Participants were randomised to placebo or 0.5 mg melatonin taken 1 hour before desired bedtime (or ~1.45 hours bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…PER3 has been studied concerning heart tissue and heart diseases, 21,34‐36 and SNPs of the PER3 gene have been confirmed to play an important role in the endocrine system and psychological disease progression. For example, effects on depression and anxiety symptoms 37 and melaton in treatment, 38 analysis of Graves’ disease susceptibility, 39 and even effects on tumors such as breast cancer 40 have been proven in previous studies. Furthermore, polymorphisms may affect physiology through unknown mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…PER3 has been studied concerning heart tissue and heart diseases, 21,34‐36 and SNPs of the PER3 gene have been confirmed to play an important role in the endocrine system and psychological disease progression. For example, effects on depression and anxiety symptoms 37 and melaton in treatment, 38 analysis of Graves’ disease susceptibility, 39 and even effects on tumors such as breast cancer 40 have been proven in previous studies. Furthermore, polymorphisms may affect physiology through unknown mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have reported the influence of ethnicity and/or race on sleep characteristics [ 132 , 133 , 134 , 135 ], which are likely impacted by genetic ancestry and social and environmental pressures. Additionally, although associations between various candidate genes (e.g., ADA , ADORA2A , PER3 ) and clinical and/or sub-clinical symptomology and conditions have been shown [ 136 , 137 , 138 , 139 , 140 ], genotypic relationships between such symptomology and neurobehavioral performance have not been directly examined in the context of sleep loss. Interindividual differences in self-rated personality traits have also been proposed as factors contributing to differences in sleep characteristics [ 141 , 142 ] and to differential vulnerability to sleep loss [ 143 ]; however, the polygenetic and complex nature of personality makes it difficult to conduct genetic studies exploring this relationship.…”
Section: Discussionmentioning
confidence: 99%